A reviewer's handbook to business valuation : practical guidance to the use and abuse of a business appraisal - Hood, L. Paul, 1960-; Lee, Timothy R. (Hoboken, N.J. : John Wiley & Sons, 2011)
Thorough guidance and detailed analysis of the valuation business engagement Discussing the practical aspects of business valuation that arise in the context of a tax valuation, this book provides you with detailed analysis of the valuation business engagement process. Detailed discussion is included of various cases outlining errors that appraisers have made in appraisal reports, as well as in-depth discussion of the current appraisal industry issues that are impacting tax valuations. Examines concepts and topics including level of value, the role of estate planners in the business valuation.
Fundamental concepts for defining value -- Defining the engagement -- Information collection and due diligence -- An overview of valuation approaches -- Valuation approaches : the cost approach.
Includes bibliographical references (pages 343-360) and index.
Print version record.
Keywords: Business enterprises -- Valuation; Corporations -- Valuation -- Law and legislation -- United States; Corporations -- Valuation -- Accounting -- Standards; Business enterprises -- Valuation; Corporations -- Valuation -- Accounting -- Standards; Corporations -- Valuation -- Law and legislation -- United States; BUSINESS & ECONOMICS -- Investments & Securities -- General; Electronic books